Captura, armazenamento e utilização de dióxido de carbono na indústria de cimento - Débora Goulart Faria (2018)
The cement industry is one of the world's largest carbon dioxide (CO2) emitters. Over the years, a number of measures have been conceived to reduce its CO2 emissions. CO2 capture technologies for storage and/or utilization are pointed out as the most relevant alternatives for significant greenhouse gases mitigation. Among CO2 capture technologies, oxy-fuel combustion has stood out due to its greater capture efficiency. For CO2 utilization, one alternative is to apply the power-to-gas technology. This work evaluated the CO2 capture, storage and utilization in the cement industry. In the simulated scenarios, oxy-fuel combustion technology was employed to CO2 capture and power-to-gas technology was applied to CO2 utilization. The clinker conventional process, the oxy-fuel combustion clinker process and the integration of oxy-fuel combustion and power-to-gas technologies was analyzed through the steady-state modeling and simulation in the commercial flowsheet simulation software Aspen Plusâ. The obtained results have shown that alternative fuels contribute to the reduction of CO2 emissions in the oxy-fuel combustion clinker process as well as in the conventional process. The calculated values of flue gas recirculation ranged from 54 to 56%. The obtained values for O2 consumption in oxy-fuel combustion ranged from 243.4 and 254.4 kgO2/tclinker. The electric energy consumption by the oxy-fuel combustion and power-to-gas technologies integration was rather high. However, values as high as 304.7 kgSNG/tclinker could be produces, which is well within the standards imposed by Brazilian laws, assuming that all CO2 was destined for utilization.